Illumination compensation in pig skin texture using local-global block analysis - Saripan, M. Iqbal; Azmi, Mohd Hafrizal; Raja Abdullah, Raja Syamsul Azmir; Anuar, Laili Hayati (Canadian Center of Science and Education, 2009)
Variable illumination in a texture is a common problem occurs to a real-time image modalities. The imbalance illumination in a texture creates virtual regions within one image, hence it affects the performance of the classification methods because it introduced an artifact patterns or virtual regions to an image. This paper presents a method to overcome the variable illumination problem in a pig skin texture using the information in the local and global blocks. The focus of this paper is to provide a fast, reliable and safe method to stabilize the lighting in an image. Pig skin texture is selected because it has a special pattern characteristic that needs to be preserved. The results show that in terms of the fluctuations contrast amplitudes in an image, the local-global method give better results than the standard homomorphic filtering technique.